Hubungan Antara Perilaku Menyimak Akun Tik Tok @Basyasman dan Perilaku Akhlak Kepada Orang Tua di Kalangan Remaja Miuslim Desa Pedurenan Parung Bogor - Nurseha Nurseha; Sri Nurul Milla (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Tik Tok is one of the popular social media among teenagers, children and even adults because Tik Tok has many interesting features so that Tik Tok users take advantage of the Tik Tok application as a means of spreading Islamic da'wah. One of the elements of success in preaching is the media as a tool, one of which is the tik tok application. There is an interest in teenagers towards the @Basyasman tik tok account to listen to the contents of the da'wah message. This study aims to determine the relationship between listening behavior to @Basyasman's tik tok account and moral behavior to parents among teenagers in Padurenan Village Rw 5. This study uses a quantitative approach with data collection techniques using questionnaires. The population of 150 teenagers in Padurenan Village Rw 5, the sample calculation used the slovin formula and the results were 60 teenagers. The data analysis technique used correlation test. The results of this study are Ha is accepted because the correlation significance value is 0.00 < 0.05 and the R value is 0.456 > 0.05 so it can be said that there is a good relationship meaning that the more moral behavior towards parents in Padurenan Village Rw 5, the better. The limitation in the study lies in the number of teenagers who not only listen to @Basyasman's da'wah, but can do this by listening to online/offline. The results of this study are used as input for adolescents to improve morals to their parents in order to produce good behavior. Keywords: Tik tok, Listening, Morals, Teenagers Village Padurenan Bogor